CONTRADICTIONS OF THE COMMUNITIES OF UNDISAN TEMBUKU BANGLI IN RESPONDING TO THE ORGANIZATION OF NGABEN IN CREMATORIUM - I Wayan Arya Adnyana; I Gusti Ngurah Sudiana; Ida Ayu Tary Puspa (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
The purpose of this study is to examine the pros and cons of holding the Ngaben ceremony at the crematorium for the people of Undisan Village, Tembuku, Bangli, Bali, and to examine the implications of the ceremony. Ngaben at the crematorium for the people of Undisan Village, Tembuku, Bangli, Bali. The data were analyzed using several theories, namely McDonaldization theory, Symbolic Interactionism Theory and Social Change Theory. This study uses a qualitative approach. The research location is Undisan Tembuku Village, Bangli, Bali. Data collection techniques were carried out through observation, interviews, and document studies. Data validity was obtained by using triangulation technique. Informants were determined purposively, and the researcher himself as the main instrument was assisted by interview guides, cameras and stationery. From the results of the study, the pros and cons of the community in the Ngaben ceremony at the crematorium are as follows. People who are pro of the equality of the Ngaben ceremony at the crematorium, the equality of sradha and devotional service, the basic equality of beliefs, changes in tradition, considerations for choosing the place for the Ngaben ceremony at the crematorium, considerations of cost efficiency, limited time, energy, and solidarity, work in the non-agricultural sector (heterogeneous), educated community groups, loosening customary sanctions in responding to social change. As for the people who are against the preservation of traditions, strengthening solidarity, employment in the agricultural sector (homogeneous), community groups with limited education, strict customary sanctions in responding to social change.